Ciclo crediticio y acelerador cambiario: evidencia empírica y consecuencias para la regulación prudencial - Jiménez Sotelo, Renzo (2010)
This paper highlights the amplifier mechanism that has the evolution of exchange rate on the credit cycle in an economy with high financial dollarization, one mechanism that has been called «the exchange rate accelerator». In this scenario, the natural procyclicality between the business cycle and credit cycle goes into the background, but perhaps not fade. The paper develops the theoretical framework underlying the transmission mechanism and shows some stylized facts of Peruvian credit system. The following presents an econometric model with panel data to estimate the effect of exchange rate accelerator on the evolution of credit default in the credit system institutions. From these empirical results, and under Basel II philosophy, the paper discusses how to implement, in banks and other credit institutions, prudential regulation that requires the allocation of provisions and capital for credit risk arising from exchange rate risk caused by foreign currency loans. The basic idea of these measures would help the system to internalize the externalities produced by this non-diversifiable risk factor.